Psychosocial working conditions, occupational groups, and risk of disability pension due to mental diagnoses: a cohort study of 43 000 Swedish twins - Åsa Samuelsson; Annina Ropponen; Kristina Alexanderson; Pia Svedberg (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: The aim of this study was to investigate associations between psychosocial working conditions, occupational groups defined by sector, and disability pension (DP) with mental diagnoses while accounting for familial confounding. METHODS: A prospective population-based cohort study was conducted, including all Swedish twins who, in January 1993, were living and working in Sweden and not on old-age pension or DP (N=42 715). The twins were followed from 1993-2008 regarding DP. Data on DP, exposures, and covariates were obtained from national registries. Cox proportional hazards regression models with hazard ratios (HR) and 95% confidence intervals (95% CI) were constructed for the whole cohort, and for discordant twin pairs. RESULTS: The associations for the whole cohort between DP with mental diagnoses and (i) job demands (HR 1.23, 95% CI 1.06-1.43), (ii) job control (HR 0.91, 95% CI 0.83-0.99), (iii) healthcare and social work (HR 1.41, 95% CI 1.04-1.92), and (iv) service and military work (HR 2.07, 95% CI 1.37-3.14) remained after accounting for possible confounders, including familial factors, while the associations between DP and (i) social support, (ii) type of jobs, and (iii) some of the occupational groups were attenuated, becoming non-significant. In the discordant twin pair analyses, commercial work was significantly associated with lower risk of DP (HR 0.55, 95% CI 0.32-0.95). CONCLUSIONS: One unit increase in job demands and working in the occupational groups healthcare and social work or service and military work seem to be risk factors of DP with mental diagnoses, independent from various background factors including familial ones. However, one unit increase in job control or working in commercial work seem to be protective factors of such DP, accounting for confounding factors of this study.